SmgGDS Is a Guanine Nucleotide Exchange Factor That Specifically Activates RhoA and RhoC - Hamel, Brant (American Society for Biochemistry and Molecular Biology, 2011)
SmgGDS is an atypical guanine nucleotide exchange factor (GEF) that promotes both cell proliferation and migration and is up-regulated in several types of cancer. SmgGDS has been previously shown to activate a wide variety of small GTPases, including the Ras family members Rap1a, Rap1b, and K-Ras, as well as the Rho family members Cdc42, Rac1, Rac2, RhoA, and RhoB. In contrast, here we show that SmgGDS exclusively activates RhoA and RhoC among a large panel of purified GTPases. Consistent with the well known properties of GEFs, this activation is catalytic, and SmgGDS preferentially binds to nucleotide-depleted RhoA relative to either GDP- or GTPγS-bound forms. However, mutational analyses indicate that SmgGDS utilizes a distinct exchange mechanism compared with canonical GEFs and in contrast to known GEFs requires RhoA to retain a polybasic region for activation. A homology model of SmgGDS highlights an electronegative surface patch and a highly conserved binding groove. Mutation of either area ablates the ability of SmgGDS to activate RhoA. Finally, the in vitro specificity of SmgGDS for RhoA and RhoC is retained in cells. Together, these results indicate that SmgGDS is a bona fide GEF that specifically activates RhoA and RhoC through a unique mechanism not used by other Rho family exchange factors.